B‐cell subpopulations in children: National reference values. Issue 3 (31st July 2014) - Duchamp, Marie; Sterlin, Delphine; Diabate, Aminata; Uring‐Lambert, Béatrice; Guérin‐El Khourouj, Valérie; Le Mauff, Brigitte; Monnier, Delphine; Malcus, Christophe; Labalette, Myriam; Picard, Capucine
Abstract Peripheral B‐lymphocytes undergo a series of changes during the first few years of life. Encounters with foreign antigens lead to maturation and differentiation. Several primary antibody deficiencies (PADs) affecting B‐cell development are associated with abnormalities in the composition and/or differentiation of B‐cell compartments. The most recent international classifications of primary immunodeficiencies (PIDs) and common variable immunodeficiencies (CVID) have highlighted the importance of B‐cell immunophenotyping and age‐specific reference intervals for diagnostic purposes. We established national reference values for memory B‐cell subpopulations, on the basis of CD27 and surface IgD expression in the peripheral blood of 242 healthy children. We report here the absolute counts and percentages of naive, switched and non‐switched memory B‐cells for seven age groups, from neonates to adults. We found that the naive B‐cells percentage declined between the ages of 6 months and 8 years, after which it remained stable at about 70–80%. Memory B‐cells are already present at birth and their numbers increase throughout childhood, stabilizing between the ages of 12 and 18 years. The definition of reference intervals for pediatric B‐cell levels should facilitate the screening and diagnosis of various B‐cell immunodeficiencies. This multicenter study, providing national reference values, should thus facilitate immunological diagnosis in children.